2020
DOI: 10.1002/adfm.202000457
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance CsPbIxBr3‐x All‐Inorganic Perovskite Solar Cells with Efficiency over 18% via Spontaneous Interfacial Manipulation

Abstract: Cesium-based all-inorganic halide perovskites solar cells (PSCs) have recently attracted increasing attention. Currently, due to the existence of high defects density and unoptimized interfacial morphology, "state-of-the-art" performances of all-inorganic PSCs are still far away from their theoretical limits. Although commonly used two-step passivation methods can effectively passivate the perovskite surface, they will inevitably detriment the original perovskite morphology due to the use of weak-polarity solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(83 citation statements)
references
References 72 publications
0
83
0
Order By: Relevance
“…To address the low volumetric energy density issue of Li–S batteries, a straightforward attempt is to construct high‐density C/S composite cathodes by using bulk sulfur or increasing the sulfur content in the cathode . However, the limited cathode conductivity caused by the presence of a large amount of electrically insulating sulfur may lead to inferior electrochemical performance . As a consequence, modest mass loadings, i.e., less than 2 mg cm −2 have been ubiquitous .…”
Section: Introductionmentioning
confidence: 99%
“…To address the low volumetric energy density issue of Li–S batteries, a straightforward attempt is to construct high‐density C/S composite cathodes by using bulk sulfur or increasing the sulfur content in the cathode . However, the limited cathode conductivity caused by the presence of a large amount of electrically insulating sulfur may lead to inferior electrochemical performance . As a consequence, modest mass loadings, i.e., less than 2 mg cm −2 have been ubiquitous .…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the excellent moisture stability of 2D perovskites demonstrated in hybrid perovskites, dimensional engineering strategy was attempted to stabilize the black phase of inorganic perovskites. [ 25,74,75,110,111 ] For instance, Zhao and coworkers first added a small amount of 2D perovskite EDAPbI 4 based on bication into CsPbI 3 perovskite precursor solution to stabilize the α ‐phase of CsPbI 3 . [ 25 ] As shown in Figure 7g,h, the EDAPbI 4 ‐based devices delivered a PCE of 11.8% and ambient and thermal stability, which were ascribed to the unique (110) layered structure of 2D perovskite EDAPbI 4 .…”
Section: Strategies For Improving Phase Stability Of Inorganic Perovsmentioning
confidence: 99%
“…The optimized PEA 2 Cs 59 Pb 60 X 181 ‐based device showed a 12.4% PCE (Figure 8b) and excellent ambient stability (Figure 8c). Zhu and coworkers [ 75 ] developed a spontaneous interfacial manipulation (SIM) method, where 2D GA 2 PbI 4 was formed on the surface 3D CsPbI x Br 3− x through adding guanidinium bromide (GABr) into CsPbI x Br 3− x precursor solution. It was revealed that spontaneously formed ultrathin 2D perovskite cannot only effectively passivate interfacial defects but also effectively protect 3D perovskite films from moisture.…”
Section: Strategies For Improving Phase Stability Of Inorganic Perovsmentioning
confidence: 99%
“…So far, over 18% PCE has been reported for PSCs based on Br-containing CsPbI 3 . [46,47] However, the addition of Br À would inevitably increase E g , demonstrating a reduction in theoretical efficiency. The amount of Br À is very important in such a kind of incorporation.…”
Section: X-site Substitutionmentioning
confidence: 99%